Extracellular vesicles in cattle infected with bovine leukaemia virus: isolation and molecular analysis - Szczotka Maria; Wasiak Magdalena; Kuźmak Jacek (Journal of Veterinary Research, 2024)
Exosomes are nanosized lipid bilayer membranous microvesicles, extracellularly released from a variety of mammalian cells. They mediate intercellular signalling by transporting several types of RNA, lipids and proteins and participate in the intercellular exchange of DNA, RNA, micro RNA, proteins and other components. These microvesicles are present in all body fluids in physiological and pathological conditions and reflect the state of the host organism. The aim of the study was the isolation and molecular determination of exosomes in blood and supernatant fluids of bovine dendritic cell cultures infected with bovine leukaemia virus (BLV).